Detection of hydroxyl and hydride functional groups in a ceria crystal under hydrogen reduction. Issue 12 (17th March 2021) - Matsukawa, Takeshi; Iida, Kazuki; Nakamura, Mitsutaka; Ishigaki, Toru
Abstract : Neutron powder diffraction analysis revealed that ceria transformed into the oxyhydroxide structure by hydrogen treatment. Abstract : Neutron powder diffraction analysis revealed that ceria transformed into the oxyhydroxide structure by hydrogen treatment. Due to detection of the vibrational modes of both OH and CeH functional groups by inelastic neutron scattering measurements, the CeH functional group was revealed to possibly exist in ceria as an aperiodic structure.